Matching Reforms to Institutional Realities : A Framework for Assessing Social Service Delivery Reform Strategies in Developing Countries - Fiszbein, Ariel; Matsuda, Yasuhiko (World Bank, Washington, DC, 2012)
The paper is based on the premise that effective institutional reforms for service delivery require a carefully-considered institutional "fitting" process as opposed to transplantation of "international best practices." The paper asks how the specific institutional contexts of a given country limit options for service delivery reforms, and therefore how a feasible set of reform options may vary systematically across countries.